Pengaruh Return on Equity (ROE), Debt Equity Ratio (DER), Earning Per Share (EPS) Terhadap Harga Saham Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2021 - Agung Meilan Supriadi; Novian Ekawaty (Jurnal Ilmiah Wahana Pendidikan, 2023)
The pharmaceutical sub-sector company is one of the companies manufacturing which has the potential to continue to be developed, as we know the Covid-19 pandemic that hit all countries in the world. That's interesting For investor interest to invest in the pharmaceutical industry. This study aims to determine whether or not the influence of the ratio of ROE, DER, and EPS to stock price. This study uses multiple linear regression analysis with SPSS version 21 and Excel 2019. The sampling technique in this study used purposive sampling to obtain a sample of 6 from 11 companies in the pharmaceutical sub-sector. Based on the results of the partial verification analysis ROE and DER variables have no effect and are not significant on stock prices and EPS has a significant effect on stock prices. Meanwhile, simultaneous ROE, DER, and EPS have a significant and significant effect on stock prices. Based on the regression Adjust R Square value of 0.513 means 51.3% of the stock price influenced by REO, DER, and EPS variables, then 48.7% were influenced by variables other than this research.